ANALISIS MINAT DAN MOTIVASI BERINVESTASI PADA GENERASI GEN-Z DI PASAR MODAL DARI PERSPEKTIF LITERASI KEUANGAN - Dhea Safitri; Vivi Adeyani Tandean (Journal Accounting International Mount Hope, 2025)
This research analyzes Generation Z's interest and motivation to invest in the capital market from a financial literacy perspective. The method used is a quantitative survey with multiple linear regression analysis. The validity test results show that all variables, namely investment motivation, financial literacy and investment interest, are declared valid, with Cronbach Alpha values ​​of 0.945, 0.989 and 0.867 respectively. The conclusion shows that investment motivation has a significant effect on investment interest (t = 15.610, p < 0.001), while investment knowledge does not show a significant effect (t = 1.217, p = 0.226). These results call for increasing financial literacy and motivation to encourage more responsible investment participation among Generation Z.